American literature from the 1850s to 1945 - Augustyn, Adam 1979-; Gale Group (New York Britannica Educational Pub. in association with Rosen Educational Services, 2011)
Examines American literature that emerged after the mid-19th century, adopting a distinct realism and an often critical view of American society. Features writers such as Henry Adams and Upton Sinclair who exposed fundamental flaws in government and industry, while Mark Twain and H.L. Mencken incisively satirized social ills such as prejudice and intolerance.
ch 1. From the Civil War to 1914 -- ch 2. American naturalism -- ch 3. Novelists and short-story writers during the world wars -- ch 4. Drama and poetry from 1914 to 1945.
Electronic reproduction.
Keywords: American literature -- History and criticism. -- 19th century; American literature -- History and criticism. -- 20th century; American literature -- 19th century -- Bio-bibliography.; American literature -- 20th century -- Bio-bibliography.; Electronic books